Arthroplasty Update - Kinov, Plamen (IntechOpen, 2013)
New technologies, developments in implant design and advances in surgical technique have improved outcomes after joint replacement and decreased rate of complications. It is not a surprise that the number of arthroplasties increases steadily every year and nowadays more than one million patients undergo the procedure annually worldwide. This book is a sequel of a successful series dedicated to one of the fastest growing fields in orthopedics - arthroplasty. Aiming at dissemination of scientific research this book provides a profound overview of the recent evolution of technology and surgical techniques. New developments of implant design and current treatment strategies have been critically discussed by the contributing authors. The process of improving care for patients and standards of treatment requires straightforward access to up-to-date research and knowledge. The format of the publication allows easy and quick reference to shared ideas and concepts. We hope, that the current book will add significant contribution to the success of this endeavor.